Global value chains and their challenge to the sustainability of exhaustible resources in the Pacific Alliance - Landa Arroyo, Yuri Jesús (2020)
In this paper we identify which global value chains made intensive use of minerals between 2005 and 2015. Input-output analysis instruments, complemented with network theory algorithms are used for this purpose. We also describe, under the weak and strong sustainability approach, the mechanisms of resource rent capture and distribution used in the Pacific Alliance countries, as well as the creation of environmental laws, which the Governments have been forced to implement given the extractive boom of the 90s and the first decade of this century.